2020
DOI: 10.1186/s12880-020-00467-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of contrast-enhanced ultrasound of breast BI-RADS 3–5 lesions

Abstract: Background: To determine the benefit of contrast-enhanced ultrasound (CEUS) in the assessment of breast lesions. Methods: A standardized contrast-enhanced ultrasound was performed in 230 breast lesions classified as BI-RADS category 3 to 5. All lesions were subjected to qualitative and quantitative analysis. MVI (MicroVascular Imaging) technique was used to derive qualitative analysis parameters; blood perfusion of the lesions was assessed (perfusion homogeneity, type of vascularization, enhancement degree). Q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
0
23
1
Order By: Relevance
“…Depiction of tumor microvascularization by CEUS may be more accurate than changes assessable by Doppler ultrasound. CEUS is increasingly used in nearly all organs [ 12 17 ]. The EFSUMB (European Federation of Societies for Ultrasound in Medicine and Biology) guidelines for the use of CEUS on nonliver application published in 2017 consider CEUS as a promising noninvasive method for the differential diagnosis of the benign and malignant thyroid nodules, but further studies are needed to explore reliable diagnostic standards [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depiction of tumor microvascularization by CEUS may be more accurate than changes assessable by Doppler ultrasound. CEUS is increasingly used in nearly all organs [ 12 17 ]. The EFSUMB (European Federation of Societies for Ultrasound in Medicine and Biology) guidelines for the use of CEUS on nonliver application published in 2017 consider CEUS as a promising noninvasive method for the differential diagnosis of the benign and malignant thyroid nodules, but further studies are needed to explore reliable diagnostic standards [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, our study lacks a point of comparison. There are similar studies, such as those on region-based quantitative classification analysis; Kapetas et al reported an AUROC of 0.812% in a cohort of 65 patients [ 47 ], Janu et al reported an AUROC of 78% in a cohort of 230 patients [ 48 ], and Park et al reported an AUROC of 0.841 in a cohort of 98 patients [ 49 ].…”
Section: Discussionmentioning
confidence: 83%
“…Our study showed significant difference in TIC parameters between tumor and normal adjacent tissue with CEUS and MRI, especially for the gradient and peak intensity, and are in line with other studies. 2 , 4 …”
Section: Discussionmentioning
confidence: 99%
“…Quantitative parameters from the examination can be used in the evaluation. 1 , 2 The contrast consists of small gas bobbles circulating in the blood without diffusion into the interstitial space, even in pathological blood vessels of a tumor. The ultrasound waves destroy the bobbles and the gas is eliminated through the lungs.…”
Section: Introductionmentioning
confidence: 99%